Single nucleotide polymorphism (SNP) panels for the estimation of dairy breed proportion and parentage assignment in African crossbred dairy cattle - CGIAR Research Program on Livestock (2021)
The research found that a single panel of 300-500 SNPs will provide high accuracy in estimation of exotic dairy proportion in West and East African crossbred cattle populations, and given the shared breed ancestral background is expected to have high accuracy in all other crossbred populations in Africa.